Engineering Microenvironment to Study Tumour Behaviour - Ayuso, José María; Ochoa, Iñaki; Fernández, Luis (Jornada de Jóvenes Investigadores del I3A, 2023)
Microtechnologies are arising as powerful tools to recreate complex biological scenarios, like tumour development and invasion.